The Legendary Saga as a Medium of Cultural Memory: A Study of AM 589a–f 4to and AM 586 4to - Valpola-Walker, Alisa (University of Cambridge, 2023)
This thesis examines the representation and historical significance of the legendary Scandinavian past in the Icelandic manuscripts AM 589a–f 4to and, to a lesser extent, AM 586 4to, both of which were produced by the same two scribes in the late fifteenth century. I begin in §1 by outlining the scholarly context, my methodology, and the sources. In §2, I provide a literary, intertextual analysis of AM 589a–f 4to, which draws on recent work on the ‘memory of literature’. In §2.1, I look at the texts in AM 589a–e 4to, focussing on how the legendary past is positioned in relation to romance. I argue that a kind of courtly culture is constructed that can accommodate traditional legendary material. This culture is depicted as originating in Troy and reaching its peak in Constantinople, with northern Europe presented as lagging behind its southern counterparts. In §2.2 and §2.3, I provide close analysis of the manuscript’s two final texts, arguing that Sturlaugs saga starfsama represents a break from tradition in its elevation of an anti-establishment protagonist who scorns the old heroic code. I contend that a new kind of hero is created in Göngu-Hrólfs saga, one who exhibits some continuity with traditional heroic values but who also participates in the culture of the manuscript’s southern courts. §2.3 concludes with a discussion of the apologiæ of Göngu-Hrólfs saga, which, by drawing attention to the boundaries of the saga as a form, reveal the limits of a purely literary approach to cultural memory. This idea is developed in §3, in which I look at ‘literature as a medium of memory’ across both AM 589a–f 4to and AM 586 4to, the latter of which I introduce in §3.1. Then, in §3.2, I examine the manuscripts’ ‘medium theory’, focussing on their relationship to orality and literacy. I argue that they participated in both spheres: they were written texts with popular appeal but were distinct from both the written texts promoted by the church and narratives circulated orally among the general population. In §3.2, I ...